Tsunami Hazard Assessment at Oeiras Municipality, Portugal - Santos, Ângela (2022)
Portugal has had several large tsunamis in the past, yet Oeiras municipality has not implemented mitigation strategies and awareness to the general public, to the authors’ knowledge. In addition, Oeiras has 10 beaches that are very popular among residents and tourists, who can become at high risk of a potential tsunami if they do not evacuate from the low ground areas on time. Thus, the tsunami numerical model of the 1755 event was carried out to calculate the inundation, complemented with a field survey, in order to assess the tsunami evacuation conditions of the beaches. The results show the tsunami hits Oeiras municipality 26 to 36 min after the earthquake, inundating all the beaches. The local tsunami hazard classification is Low on 3 beaches, Moderate on 1 beach, High on 5 beaches, and Critical on 1 beach. In addition, there are no tsunami evacuation signs to guide the people to move to higher ground. Therefore, it is important to conduct mitigation strategies to avoid and reduce fatalities in a future tsunami.